Device exchange versus nonexchange modalities in left ventricular assist device‐specific infections: A systematic review and meta‐analysis. Issue 5 (25th November 2018) - Bauer, Tyler M.; Choi, Jae Hwan; Luc, Jessica G.Y.; Weber, Matthew P.; Moncho Escrivá, Ester; Patel, Sinal; Maynes, Elizabeth J.; Boyle, Andrew J.; Samuels, Louis E.; Entwistle, John W.; Morris, Rohinton J.; Massey, H. Todd; et al.
Abstract: No standardized treatment algorithm exists for the management of continuous‐flow left ventricular assist device (CF‐LVAD)‐specific infections. The aim of this systematic review and meta‐analysis was to compare the outcomes of CF‐LVAD‐specific infections as managed by device exchange to other treatment modalities not involving device exchange. Electronic search was performed to identify all studies in the English literature relating to the management of CF‐LVAD‐specific infections. All identified articles were systematically assessed for selection criteria. Thirteen studies with 158 cases of CF‐LVAD‐specific infection were pooled for analysis. Overall, 18/158 (11.4%) patients underwent CF‐LVAD exchange, and 140/158 (88.6%) patients were treated with non‐exchange modalities. The proportion of patients with isolated driveline infections or pump or pocket infections did not differ significantly between the groups. During a mean follow‐up of 290 days, there were no significant differences in the overall mortality [exchange 17.6% (4.3–50.6) vs. non‐exchange 23.3% (15.8–32.9), P  = 0.67] and infection recurrence rates [exchange 26.7% (8.7–58.0) vs. non‐exchange 38.6% (15.4–68.5), P  = 0.56]. In the setting of CF‐LVAD‐specific infections, device exchange does not appear to confer an advantage in the overall mortality and infection recurrence as compared to non‐exchange modalities.